(untitled) (Development Service Industry Management, 2024)
The formation of a regional management system of hospitality enterprises is justified by the presence of a number of factors, in particular, such as military actions, and hence the high degree of uncertainty of the market situation, seasonal instability of demand for hotel services, increased competition in the tourism business, lack of financial resources, the impossibility of solving problems outside enterprises, etc. For any region, the formation of an effective system of management of enterprises in the field of hospitality should be based on the regional strategy of socio-economic development, analysis of the external and internal environment, territorial features, regional marketing and the regularities of the operation of hotels, catering establishments, tourist and animation enterprises and other enterprises in the field hospitality The formation of a regional management system for hospitality enterprises will contribute to increasing the efficiency of the operation of hospitality enterprises, improving the quality of service provision, and eliminating unmanaged elements that are not affected by the internal management system of the enterprise. The purpose of the study is the theoretical and methodological substantiation of the processes of formation of the regional management system of hospitality enterprises, in particular, the establishment of approaches and principles, as well as the definition of tasks, the solution of which must precede the formation of the regional management system of hospitality enterprises. The methodological basis of the study was the study of foreign experience, the use of methods of analysis and synthesis, to determine theoretical approaches and models of regional management of hospitality enterprises, surveys, to determine tasks, the solution of which should precede the formation of a regional management system of enterprises in the field of hospitality and the establishment of features of the border region, modeling, for the development of a regional management model for hospitality enterprises. On the basis of the analysis of information sources, separate theoretical approaches to the formation of a regional management system of hospitality enterprises have been determined, and attention has been focused on the theory of incrementalism, which can become the optimal methodological approach to decision-making in today’s unstable conditions and involves a moderate, gradual movement, breaking down large problems into smaller ones. using the "trial and error" method. The problems that need to be solved in the formation of the regional management system of hospitality enterprises are identified, which include environmental, social, legal regulation, effective management of human resources, variability of the market environment, information security, etc., on the basis of which the basic approaches to the formation are identified of the regional management system of hospitality enterprises - ecological, social and economic. On the example of Chernivtsi region, a survey of hotel and restaurant business managers, tourist enterprises and entertainment establishments was conducted, which contributed to the definition of tasks, the solution of which should precede the formation of a regional management system for hospitality enterprises and the identification of the features of the border region. Analysis of the activities of hospitality enterprises of the Chernivtsi region and the above-mentioned approaches made it possible to determine the main principles of the formation of the regional management system, which together contributed to the development of a regional model of management of enterprises in the field of hospitality in the region. Theoretical and methodological substantiation of the process of formation of the regional management system of hospitality enterprises will contribute to the improvement of the management of hotel, restaurant and tourist business enterprises, increasing the efficiency of their functioning and eliminating problems arising in the external environment of hospitality enterprises. Prospects for further research consist in determining and substantiating the key performance indicators of the regional management system of hospitality enterprises and researching the processes of price policy formation of hospitality enterprises based on demand forecasting (revenue management) aimed at ensuring high profitability.